2022
DOI: 10.1369/00221554221114174
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved and Highly Multiplexed Protein and RNA In Situ Detection by Combining CODEX With RNAscope In Situ Hybridization

Abstract: Highly multiplexed protein and RNA in situ detection on a single tissue section concurrently is highly desirable for both basic and applied biomedical research. CO-detection by inDEXing (CODEX) is a new and powerful platform to visualize up to 60 protein biomarkers in situ, and RNAscope in situ hybridization (RNAscope) is a novel RNA detection system with high sensitivity and unprecedent specificity at a single-cell level. Nevertheless, to our knowledge, the combination of CODEX and RNAscope remained unreporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Five µm FFPE tissue sections of selected samples sectioned 5 were cut and mounted on poly-L-lysine coated coverslips. Akoya Biosciences CODEX multiplex immunostaining (CODEX) and ACDbio RNAscope HiPlex v2 (12-plex) multiplex FISH (RNAscope) were each performed according to their respective manufacturer's instructions (kits used are listed in Supplemental Table S8), and combined in sequence as previously described, with slight modifications 82 .…”
Section: Multiplex Immunostaining Followed By Multiplex Fishmentioning
confidence: 99%
“…Five µm FFPE tissue sections of selected samples sectioned 5 were cut and mounted on poly-L-lysine coated coverslips. Akoya Biosciences CODEX multiplex immunostaining (CODEX) and ACDbio RNAscope HiPlex v2 (12-plex) multiplex FISH (RNAscope) were each performed according to their respective manufacturer's instructions (kits used are listed in Supplemental Table S8), and combined in sequence as previously described, with slight modifications 82 .…”
Section: Multiplex Immunostaining Followed By Multiplex Fishmentioning
confidence: 99%
“…Formalin-fixed paraffin-embedded MesLNs tissues collected from the necropsied animals LC31, LB66, DJ01, and EM77 were studied using the combination of CODEX and RNAscope in situ hybridization by following our reported method ( 10 ) in a single slide from each animal. Briefly, a 6-μm tissue section on a coverslip was deparaffinized, hydrated, and pretreated with 3% hydrogen peroxide for 10 min at room temperature, boiled in citrate buffer (pH 6, Sigma-Aldrich, catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…ATI-1 was intended to evaluate the timing and extent of viral rebound in plasma and composition of viral clonotypes in peripheral blood after long-term ART and to examine the potential influence of a prior ATI on viral barcodes detected after a subsequent ATI. One week after the second ATI (post–ATI-2), when all macaques still had plasma viral RNA loads below 22 copies/ml, necropsies were performed, and multiple tissues, including the mesenteric LNs (MesLNs), inguinal LNs (IngLNs), spleen, ileum, colon, lung, liver, and brain and blood, were examined by viral barcode sequencing, analysis of cell-associated DNA (CA-DNA) and cell-associated RNA (CA-RNA), intact proviral DNA assay (IPDA), combined co-detection by indexing (CODEX) and RNAscope (Comb-CODEX-RNAscope) in situ hybridization ( 10 ), single-cell RNA sequencing (scRNA-seq), and other approaches. The results suggested that, among the tissues studied, MesLNs, IngLNs, and spleen showed overlap with viral barcodes detectable by sensitive sequencing of plasma at necropsy, suggesting that these tissues may contribute to viral reactivation and eventual rebound after ATI.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the respective HMTI methods are not necessarily confined to the detection of a single type of target molecule. Recent concepts and protocols have describe simultaneous or successive imaging of both proteins and RNA in tissue, e.g., by including RNAscope®-derived branched DNA constructs with metal-tagged label probes in IMC panels [ 23 ], or combining CODEX and RNAscope® [ 28 ]. The SM-omics platform achieves further integration of synergistic readouts, as it combines antigen detection with DNA-barcoded antibodies with spatial transcriptomics in one analytic system [ 29 ].…”
Section: Synergistic Potential With Spatial Transcriptomics and Spati...mentioning
confidence: 99%